Descrevendo o patrimônio documental da FURG: Faculdade de Direito Clovis Bevilaqua (1959-1972) - Santos, Andrea Gonçalves dos (2012)
In 1959 it was settled in the city of Rio Grande, the Law School Clovis Bevilaqua, belonging to the Universidade Católica de Pelotas and maintained by Mitra Diocesana de Pelotas and subsequently forming the Universidade do Rio Grande - URG until 1972. This research is justified by historical and cultural value of its collection not only for the institution but also to the entire local community. Towards the presented, this paper aims to describe, according to the Brazilian standard archival, the collection of the Law School Clovis Bevilaqua, between the periods 1959 to 1972, in order to preserve institutional memory and provide access to information. Were addressed documentary heritage and as part of this university archive and its relationship with the Archival science, giving focus to the description, the creation of finding aids and the use of Information Technology (IT) grounded in the National Politics of Archives. The research is of an applied nature, descriptive, qualitative and set up a case study. Priority was given to the identification, collection and organization of the documentation that was dispersed in the institution. Also took place preventive conservation actions. The collection of information was performed by the research literature and documents. This work allowed to identify and propose policies for archival fonds of documents of the institution, developing a descriptive framework of fonds; Make the description of the background and documentary series, according to Nobrade and; analyze the ICA-AtoM as software for archival description of documents within the archive system s - SIARQ of the institution. Currently this software is being analyzed by the Division Support of FURG for adoption at the institutional level. Thus, this paper presents the research products generated as an instrument broad and comprehensive, the Arquivo Geral s guide fonds and a specific Inventory Law School Clovis Bevilaqua. Both products, aim access to information as a mean to collaborate in the development, transmission, preservation and diffusion of knowledge developed in the institution. It should be emphasized, above all, the importance of the continuity of this process in various documentary funds at FURG as a way to preserve the documentary heritage and memory of the institution of higher education in the region.